Evaluation Village-Owned Enterprise Program Through Utilization of Potential Agricultural Sector in Tokbesi Village - Maria Elfrida Ina Makin; Agustinus Longa Tiza; Hendrikus Hironimus Botha; Surya Yudha Regif; Muhammad Imanuddin Kandias Saraan (Talenta Publisher, 2023)
Village-Owned Enterprises can capitalize on the agriculture sector's potential for the benefit of rural residents. Thus, the goal of this research is to describe how the economic operations of Village-Owned Enterprises in Tokbesi Village capitalize on the agricultural sector's potential. This study employs the qualitative descriptive research method. The study's goal was to assess the Tokbesi Village-Owned Enterprises program using Dunn's evaluation criteria, which included effectiveness, efficiency, adequacy, alignment, responsiveness, and correctness. In this study, informants and documents served as data sources. Techniques for analyzing data include data reduction, data display, and making conclusions. The research findings indicate that implementing the Village Owned Enterprise program in Sesa Tokbesi has yet to be maximized due to obstacles such as uncontrolled financial management, transportation facilities to facilitate business units, and miscommunication between administrators. The program's implementation could have helped alleviate poverty and raise Village's Original Income. Still needing to be capable of developing every business unit, particularly in the agriculture sector. Village governments can provide funding opportunities to local food and agriculture entities. The Village Government might create educational institutes and personnel resource training to increase its administrative capacities and skills. Future research is needed to observe village governments plan programs to fulfill the aims of expanding the agricultural industry and boosting the welfare of rural populations.